Pottermore secrets and mysteries revealed : the unofficial guide to Pottermore.com - Rich, Jason R. (Que, 2013)
'Pottermore' is J.K. Rowling's new multiplayer gaming environment and global community for millions of passionate Harry Potter fans of all ages. This guide offers simple, visual explanations of game areas that users may find confusing, helping young fans have more fun and helping their parents keep them safe.